Kewenangan Kreditur dalam Menjual Obyek Jaminan Tanah dan Bangunan Letter C tanpa Melalu Lelang - Hidayati, Nuri; Permadi, Iwan; Santoso, Budi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
The purpose of this study is to describe the authority of creditors to direct sell warranty objects in the form of land and building Letter C without passing the auction. This study uses normative juridical research methods that study and analyze the application of rules, acts, positive legal norms contained in legislation, jurisprudence, and contracts. This study uses a statutory approach, a conceptual approach, and a case approach. The results show that creditors are authorized to sell warranty objects in the form of land and Letter C buildings without auctions but through underhand sales.